Interpersonal Meaning in Public Communication Strategy - Tyaningsih, Annisa Rachmani; Palapah, Maya Amalia Oesman; Hernawati, Riza; Samyah, Amira Hazari; Nurmawan, Aldisha Putri (KnE Social Sciences, 2023)
The outbreak of unfiltered and uncontrollable information during the COVID-19 pandemic era has given rise to the phenomenon known as the ”infodemic.” This phenomenon has caused confusion and instilled fear among the public. The infodemic has made it challenging for people to access accurate, credible, and reliable sources of guidance, resulting in public distrust. In response, governments have taken direct action by establishing COVID-19 Task Forces at national and institutional levels. These task forces serve as the frontline in providing directions and information to the public about COVID-19. To fulfill this role, COVID-19 Task Forces in universities have made efforts to design communication strategies that can earn the trust of the community. This study aims to identify the public communication strategies employed by two universities, namely Universitas Islam Bandung (UNISBA) and Universitas Pendidikan Indonesia (UPI). The focus will be on the use of interpersonal meaning in delivering the message. The research utilizes a qualitative method with a case study approach. Data collection techniques involve in-depth observation interviews, literature review/documentation, and focus group discussions (FGDs). The data analysis employs interpersonal meaning analysis based on Halliday’s framework. The results reveal that each university adopts a distinct interpersonal meaning as their public communication strategy to portray their institutional image. Keywords: Covid-19 task force, interpersonal meaning, public communication strategy